Demographic Influences on Eating Behaviors among Young Adults in Barangay Indahag, Philippines: A Descriptive-Correlational Study - Agbayani, Nikka; Arbutante, Ashley Blaise; Bagares, Lebby Reyss; Barcelona, Angela Camelle; Bonita, Nicole Christy; Cagulada, Trisha Mikaela; Casulo, Vince Edward; Chung, Victoria Dorothy; Collera, Gwyneth Alexis; Dacalos, Arvie Gen Alijandro; Santos, Ellenita De los; Araune, Paolo; Vera, Glenda De (International Journal of Nursing and Health Services (IJNHS), 2025)
Background & Aim: Eating behaviors are vital health indicators, particularly among young adults aged 20-37, warranting attention in communities like Barangay Indahag, Philippines. This study analyzed how demographic factors influence eating habits in this context. Utilizing Sister Callista Roy's Adaptation Model, associations between gender, occupation, socio-economic status, physical activity, and food choices were explored to inform interventions promoting healthier eating. Methods & Materials: Employing a descriptive-correlational research design. Surveys and a modified questionnaire based on the Dutch Eating Behavior Questionnaire collected data on restrained, emotional, and external eating behaviors. Statistical analyses, including the F-test, ANOVA, and T-tests, identified significant associations between demographic variables and eating behaviors. Results: Gender differences were significant, with females exhibiting higher levels of restrained eating while males showed more external and emotional eating behaviors. Females tended to be more weight and appearance-conscious, while males leaned towards indulging in appealing food options. No significant disparities were found based on occupation, socio-economic status, or weekly physical activity. Conclusion: Most respondents were females, unemployed, and had low incomes, engaging primarily in household physical activities and consuming high-calorie foods. Predominantly exhibiting External Eating Behavior, restrained eating was rare, and emotional eating was absent. Recommendation: Clinical practitioners in Barangay Indahag should prioritize interventions aimed at addressing gender-specific eating behaviors, such as restrained eating among females and external/emotional eating among males, to promote healthier eating habits and reduce the risk of eating disorders.